Ang hidden curriculum at edukasyon sa pagpapahalaga perspektibo mula sa antropolohiya - Abuso, Julian Elloso
This essay elaborates the hidden curriculum is a cultural process that influences values formation among students. Because teachers serve as models, the paper argues that they ought to demonstrate through examples the values they transmit to their students.
Keywords: Values -- Philippines; Moral education -- Philippines